Post-communism structural changes of the Romanian forestry sector - Іоан Васіле Абрудан (Науковий вісник НЛТУ України, 2019)
Forests cover 28 % of the land area of Romania and, they are important from the ecological, economic and social perspectives. Political initiatives to restore property to its pre-nationalization (1948) forest owners became a reality, after the fall of communism. Compared to the other former communist countries from Central and Eastern Europe, the forest restitution process in Romania took a longer time and has been legally implemented via three successive restitution laws in a period of 15 years: Law 18/1991, Law 1/2000 and Law 457/2005. By the successive implementation of these forest restitution laws, the total forest area restituted to the non-state forest owners reached 3.15 million ha at the beginning of 2017, representing about half of the total forest area in Romania. The institutional changes in the forestry sector have been politically influenced (both by the Government and European Union) and not always responsive to the sector needs, realities and evolution. Whilst during the communist period, all typical sectoral functions such as regulatory, supervisory, management and ownership were under the responsibility of the same entity – the Ministry of Forests, in early 1990 s the regulatory and supervisory functions of the state were separated from the management function as the National Forest Administration (NFA)-Romsilva was established as the management entity of state forests, mainly with a commercial mandate. The move of the Department of Forests (the public authority responsible for forests in Romania) under different ministries in the last three decades was accompanied by many changes of the subordinated units and disruptions in the normal activity of its staff. Regarding the forest control and supervisory functions at regional level, 7 regional Forest Inspectorates were established in 1999, their number being increased to 16 in 2001. After 2003 they have had a tumultuous evolution, with several changes of mission and subordination and in 2015, the Forest Inspectorates were transformed into Forest Guards. A significant institutional milestone in the post-communist development of the forestry sector in Romania was the establishment of the first "private" forest districts (administrative/management legal entities for non-state forests, similar to those of NFA-Romsilva) in 2002: their number reached 145 in 2017, managing more than 1.7 million ha of forests. The radical change in forest ownership continues to pose a high pressure on the restructuring of the forest institutions, administration and management structures. It is expected that the decentralisation and reduction of state role in forest administration and management will continue in the next decade.